Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41598-017-02850-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and immunobiological characterization of retinoic acid inducible gene-I-like receptor expression in mesenchymal stromal cells

Abstract: Due to their immunomodulatory and regenerative properties, Mesenchymal stromal cells (MSC) have generated major interests in several clinical settings including transplantation and inflammatory diseases. MSC functions can be influenced by their tissue origin. Their microenvironment strongly affects their biology notably through TLR sensing. In this study, we show that MSC isolated from four different sources express another type of cytosolic pathogen recognition receptors known as retinoic acid inducible gene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…These results validated the use of this protocol (brief stimulation of rBM-MSCs with Poly(I:C) for 1 h) and are in agreement with previous studies reporting the expression of TLR3 mRNA by mouse and human BM-MSCs (mBM-MSCs and hBM-MSCs, respectively) [15, 5558]. These findings are also in line with the work by Raicevic et al, who reported that hBM-MSCs express functional MDA5 [59]. In their study, Poly(I:C) internalization was facilitated by the transfection reagent LyoVec, an approach that has been shown to stimulate retinoic acid-inducible gene- (RIG-) I-like receptors (RLR), such as MDA5, rather than TLR3 [60, 61].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results validated the use of this protocol (brief stimulation of rBM-MSCs with Poly(I:C) for 1 h) and are in agreement with previous studies reporting the expression of TLR3 mRNA by mouse and human BM-MSCs (mBM-MSCs and hBM-MSCs, respectively) [15, 5558]. These findings are also in line with the work by Raicevic et al, who reported that hBM-MSCs express functional MDA5 [59]. In their study, Poly(I:C) internalization was facilitated by the transfection reagent LyoVec, an approach that has been shown to stimulate retinoic acid-inducible gene- (RIG-) I-like receptors (RLR), such as MDA5, rather than TLR3 [60, 61].…”
Section: Discussionsupporting
confidence: 92%
“…In their study, Poly(I:C) internalization was facilitated by the transfection reagent LyoVec, an approach that has been shown to stimulate retinoic acid-inducible gene- (RIG-) I-like receptors (RLR), such as MDA5, rather than TLR3 [60, 61]. Although the activation of RLR can trigger cell death, Raicevic et al showed that only prolonged stimulation (48 h) with high doses of Poly(I:C) in conjunction with LyoVec (but not with Poly(I:C) alone) can induce cell death in hBM-MSCs [59]. Our results agree with these findings, indicating that a brief exposure to Poly(I:C) for 1 h does not affect the viability of rBM-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, a report by Krampera attributed IFN-γ priming of bone marrow-derived MSCs to the enhancement of immunomodulatory proteins, mainly IDO1 79 . Similar observations were also described for poly(I:C), a well-known analog of dsRNA 80 82 , and BiP/Glucose-Regulated Protein 78 (GRP78) 83 90 , albeit IFN-γ has been investigated most intensively. The ability of type II interferon for inducing the expression of immunoregulatory encountered genes, including IDO1 , in MSCs from different sources was previously reviewed 91 , 92 .…”
Section: Discussionsupporting
confidence: 67%
“…Thus, NLR-inflammasome represents an alternative (to interferon type II) and very damaging route of responses to PAMPs [ 27 ]. The RLR activation by RNA viruses in numerous non-immune cells also leads to type I and III interferon production [ 28 , 29 ]. The upregulation of interferon and interferon response pathways helps limit viral replication, but since these defense pathways are accompanied by apoptosis it may contribute to slow immune reconstitution and immune complication, such as IRIS [ 30 ].…”
Section: Interferon Type I Iiimentioning
confidence: 99%